FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI DALAM LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR 2007-2012 - , DIAN KUSUMASARI, Drs. Irfan Nursasmito, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to prove factors that influence of Corporate Social Responsibility (CSR) disclosure in the annual report of manufacturing company 2007-2012. Factors influencing corporate social responsibility (CSR) disclosure in this study are company size, profitability, management ownership, and public ownership. The populations in this study are all companies listed on the Indonesia Stock Exchange 2007-2012 and sample selected using purposive sampling method. Hypothesis testing using multiple regression. The results showed that company size and management ownership have a positive influence on CSR disclosure, while profitability and public ownership have no effect on CSR disclosure.